Changes of Immunological Profiles in Patients with Chronic Myeloid Leukemia in the Course of Treatment - Zuzana Humlová; Hana Klamová; Ivana Janatková; Karin Malícková; Petra Králíková; Ivan Šterzl; Zdeněk Roth; Eva Hamšíková; Vladimír Vonka (Clinical and Developmental Immunology)
In the previous paper of ours we compared, prior to start any treatment, a number of immunological parameters in 24 chronic myeloid leukemia patients with the same number of healthy subjects matched by age and sex. We found significant differences in the levels of immunoglobulins, the C4 component of complement, the C-reactive protein, interleukin 6, the composition of lymphocyte population and the production of some cytokines by stimulated CD3+ cells. Eleven of these patients were followed longitudinally. After treatment with hydroxyurea, interferon alpha, imatinib mesylate and dasatinib, or various combinations thereof, hematological remission was achieved in all patients and complete cytogenetic remission in nine of them. There was a nearly general tendency towards normalization of the abnormalities observed in the patients at their enrollment.